2015
DOI: 10.1080/21513732.2015.1055338
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of willingness to pay for community-based conservation activities at the Ghodaghodi Lake Complex, Nepal

Abstract: Wetlands comprise an important ecosystem but are under threat in developing countries due to increasing human encroachment. Community-based conservation is an approach for sustainable management of the wetlands near settlements. This study investigated willingness to pay of local people for community-based conservation activities and the variables affecting it in the Ghodaghodi Lake Complex, Nepal. A sample of 217 households residing near the lake complex was surveyed. The result showed that households were wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
11
23
1
5
Order By: Relevance
“…Community involvement in ecosystem conservation and tourism activities is another important aspect in making tourism a successful venture in natural attraction sites. The GLC is bounded by three politico administrative units, and Lamsal et al (2015a) reported that local people depend on wetland resources at the GLC, which contribute to 12.5% of their gross household annual income. This resource dependency means there is an opportunity to push locals towards tourism activities, which on one hand would assist in the conservation of existing endangered flora and fauna habitats, while on the other hand would provide more diversified livelihood opportunities through tourism employment and small trades and businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Community involvement in ecosystem conservation and tourism activities is another important aspect in making tourism a successful venture in natural attraction sites. The GLC is bounded by three politico administrative units, and Lamsal et al (2015a) reported that local people depend on wetland resources at the GLC, which contribute to 12.5% of their gross household annual income. This resource dependency means there is an opportunity to push locals towards tourism activities, which on one hand would assist in the conservation of existing endangered flora and fauna habitats, while on the other hand would provide more diversified livelihood opportunities through tourism employment and small trades and businesses.…”
Section: Discussionmentioning
confidence: 99%
“…De igual forma Tian et al (2020) en su estudio percepciones de los servicios de los ecosistemas, perjuicios y la disposición a pagar por la conservación de espacios verdes urbanos en China, revelan que la mayoría de los encuestados (90.7%) presentan una disposición a pagar. Contrario a lo expuesto anteriormente, pero no muy alejado, Lamsal et al (2015) reportó sobre la DAP por actividades de conservación basadas en la comunidad en el Complejo del Lago Ghodaghodi, Nepal, donde todos los encuestados están dispuestos a apoyar el programa de conservación, el 39% a través de tasas mayores, mientras que el 61% mostró una DAP más baja. Por lo tanto, es probable que la DAP alta es producto de las prioridades y el interés colectivo de la población local para actividades de conservación basadas en el beneficio común.…”
Section: Discusión Discusiónunclassified
“…Gordillo et al (2019) en su estudio de implementación de un programa para frenar la deforestación en Ecuador, la variable edad presento una probabilidad positiva menor en personas mayores. Por otro lado, Alarcón et al (2018), Lamsal et al (2015 y Pham et al (2018) reportaron que, si bien la variable edad es positiva correlacionada con programas de conservación del bosque, es muy poco probable que personas mayores contribuyan al pago, lo cual coincide con nuestros resultados.…”
Section: Discusión Discusiónunclassified
“…Para el primer caso las variables EDU y ACT son determinantes en la DAC, lo que expresa que el nivel educación de sus miembros y el conocimiento de las actividades que mayor impacto generan a la comunidad, podrían en algún momento favorecer la implementación de un plan de desarrollo, resultados que están respaldados por los hallazgos de Amare et al (2016); Kwon, Kim, y Yoo (2018); Lamsal, Atreya, Pant, y Kumar (2015); Pham et al (2018); Seroa y Ortiz (2018). Para el segundo caso, Puerto Arturo al ser una comunidad más organizada y haber frenado por decisión comunal a la minería de oro, se desarrollan gestionando sus recursos de manera sustentable; recolección de B. excelsa (castaña), extracción de madera y agroforestería, por lo que los Ingresos y los Peligros potenciales son decisivos para aceptar un plan de desarrollo con fines de conservación, mostrando su consistencia con estudios reportados por Hjerpe y Hussain (2016); Iranah, Lal, Wolde, y Burli (2018); Lamsal et al (2015); Pham et al (2018); Ramli et al (2017); Tolunay y Başsüllü (2015).…”
Section: Valor De Conservación En Bosques De Comunidades Indígenas: Uunclassified